PTH-038 Diagnostic utility of further assessment with endoscopic ultrasound in patients with unexplained common bile duct obstruction with and without abnormal liver enzymes. (22nd June 2015) - On, W; Lim, Y; Patani, O; Kapoor, N
Abstract : Introduction: Patients who undergo endoscopic ultrasound (EUS) are often referred because of a dilated common bile duct (CBD) of unknown cause and/or abnormal liver enzymes (LFT). We aimed to determine the diagnostic yield when such patients are referred for an EUS for further assessment. Method: All patients who underwent an EUS in 2010 were included. Patients who had an identifiable cause of pathology on prior imaging were excluded. We retrospectively analysed our electronic database for radiological evidence of CBD dilatation, laboratory values of LFT and results of the EUS. Results: 184 patients were identified. 60 (32.6%) had a dilated CBD with normal LFT (group A), 65 (35.3%) had dilated CBD with abnormal LFT (group B), 36 (19.6%) had abnormal LFT with a normal CBD (group C), and 23 (12.5%) had normal LFT with a normal CBD (group D). Out of 184 patients, 78 (42.4%) received a diagnosis at EUS. The diagnostic yield of EUS when divided into groups were: A = 23.3% (14/60), B = 55.4% (36/65), C = 55.6% (20/36), D = 34.8% (8/23). There was a significant difference in diagnostic yield between groups A vs B and A vs C (p = <0.05). When comparing patients with abnormal LFT (B+C) against patients with normal LFT (A+D), there was also a significant difference (p = <0.05). Conclusion: Patients with abnormal LFT were more likely to have a positive diagnosis at EUS than those with a dilated CBD. However there were substantive positive findings in all groups justifying further assessment with EUS even if prior imaging tests were normal. Disclosure of interest: None Declared.